Cultural technologies of modern music science (Pedagogy of Higher and Secondary Education, 2009)
The article is dedicated to questions music history metaphysicians, who Defines the regular nature of the appearance in big history rime of the atradicionalizm and accordingly, regularity of the manifestation in art and in music effect modernist style-avanguard in the manner of single extreme стилевого of the complex, which reflect in category culture - a music civilization, primary - a secondary genres.
Keywords: historical metaphysics; music style; modem-avanguard